SINTESIS HASIL PENELITIAN MEMBACA SEBAGAI LANDAS PIJAK PENYUSUNAN PEMBELAJARAN MEMBACA DALAM BINGKAI KURIKULUM 2013 - Erisy Syawiril Ammah (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2016)
This article tries to collect some of the results ofresearch on learning to read in school. The results of thesestudies are reviewed in order to be used as the basis for thepreparation of learning to read a good program. This is becauseof the fact until now that learning to read for students not to runup as expected. Students' reading ability is still far behindneighboring countries. The use of text-based curriculum in 2013which should help the program of learning to read in school, butin reality these capabilities also can not be improvedsignificantly. Once reviewed by the research results in thispaper , learning to read for the student was influenced somethings, especially with regard to strategy, media, andtechniques of reading, which is in use adjusted based on thelevel and character of students .